1981
DOI: 10.1128/iai.33.2.401-406.1981
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhea in lambs: experimental infections with enterotoxigenic Escherichia coli, rotavirus, and Cryptosporidium sp

Abstract: Thirteen gnotobiotic lambs, aged from a few hours to 8 days, were inoculated orally with single infections of enterotoxigenic Escherichia coli (ETEC) (four animals), lamb rotavirus (five animals), and Cryptosporidium (four animals). Six gnotobiotic and two specific-pathogen-free lambs were co-inoculated with either rotavirus and ETEC (four animals), rotavirus and Cryptosporidium (two animals), or ETEC and Cryptosporidium (two animals). Lambs 4 days of age and older became only subclinically infected with eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…These experiments confirm previous observations that co-infection of calves with ETEC and rotavirus can induce diarrhoea in circumstances where one agent acting alone does not (Tzipori et al, 1981a). Similar observations were made in foals (Tzipori et al, 1982a, b) inoculated with rotavirus and the same ETEC, while dual infection failed to precipitate a disease in lambs older than 3 days (Tzipori et al, 1981b). It was surprising that the ETEC serotype used in these experiments, although possessing K99, failed to adhere to the mucosal lining of the small intestine of newborn calves.…”
Section: Discussionsupporting
confidence: 90%
“…These experiments confirm previous observations that co-infection of calves with ETEC and rotavirus can induce diarrhoea in circumstances where one agent acting alone does not (Tzipori et al, 1981a). Similar observations were made in foals (Tzipori et al, 1982a, b) inoculated with rotavirus and the same ETEC, while dual infection failed to precipitate a disease in lambs older than 3 days (Tzipori et al, 1981b). It was surprising that the ETEC serotype used in these experiments, although possessing K99, failed to adhere to the mucosal lining of the small intestine of newborn calves.…”
Section: Discussionsupporting
confidence: 90%
“…In the lamb that was killed 24 hours after infection the number of E. coli S 13 in the intestinal contents indicated that multiplication had occurred, which appears to be limited subsequently by antagonistic mechanisms in the intestine. TZIPORI et al (1981) found that after gnotobiotic lambs, aged 5 days or more, had been inoculated with lolo E. coli S 13 colonisation of the intestine did not occur and they suggested that there may be a close correlation between adherence, colonisation and clinical diarrhoea on the one hand and the age of the lamb on the other.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental coinfections with ETEC and rotavirus in gnotobiotic calves have shown both a synergistic interaction producing a fatal disease and an interaction in which rotavirus aided ETEC colonisation but with little disease enhancement (RUNNELS et al, 1980). In gnotobiotic lambs, TZIPORI et al (1981) found that co-infection of 4-8 day-old lambs failed to induce diarrhoea.…”
Section: Introductionmentioning
confidence: 99%
“…Ovines In ovines, the rotaviruses are known to cause enteritis and diarrhea, especially in neonatal lambs (Theil et al 1996, Wani et al 2004. Other infectious agents that may cause neonatal diarrhea in lambs are E. coli and Cryptosporidium (Tzipori et al 1981;Ellis and Daniels 1988). Besides the commonly seen group A ovine rotaviruses (ORV), atypical group B viruses may also cause the infection in ovines (Holland 1990;Theil et al 1996).…”
Section: Disease In Other Domestic Animalsmentioning
confidence: 99%